A Study of Gibberellin Homeostasis and Cryptochrome-Mediated Blue Light Inhibition of Hypocotyl Elongation - Zhao, Xiaoying (American Society of Plant Biologists, 2007)
Cryptochromes mediate blue light-dependent photomorphogenic responses, such as inhibition of hypocotyl elongation. To investigate the underlying mechanism, we analyzed a genetic suppressor, scc7-D (suppressors of cry1cry2), which suppressed the long-hypocotyl phenotype of the cry1cry2 (cryptochrome1/cryptochrome2) mutant in a light-dependent but wavelength-independent manner. scc7-D is a gain-of-expression allele of the GA2ox8 gene encoding a gibberellin (GA)-inactivating enzyme, GA 2-oxidase. Although scc7-D is hypersensitive to light, transgenic seedlings expressing GA2ox at a level higher than scc7-D showed a constitutive photomorphogenic phenotype, confirming a general role of GA2ox and GA in the suppression of hypocotyl elongation. Prompted by this result, we investigated blue light regulation of mRNA expression of the GA metabolic and catabolic genes. We demonstrated that cryptochromes are required for the blue light regulation of GA2ox1, GA20ox1, and GA3ox1 expression in transient induction, continuous illumination, and photoperiodic conditions. The kinetics of cryptochrome induction of GA2ox1 expression and cryptochrome suppression of GA20ox1 or GA3ox1 expression correlate with the cryptochrome-dependent transient reduction of GA(4) in etiolated wild-type seedlings exposed to blue light. Therefore we propose that in deetiolating seedlings, cryptochromes mediate blue light regulation of GA catabolic/metabolic genes, which affect GA levels and hypocotyl elongation. Surprisingly, no significant change in the GA(4) content was detected in the whole shoot samples of the wild-type or cry1cry2 seedlings grown in the dark or continuous blue light, suggesting that cryptochromes may also regulate GA responsiveness and/or trigger cell- or tissue-specific changes of the level of bioactive GAs.